2023
DOI: 10.1039/d3qi00432e
|View full text |Cite
|
Sign up to set email alerts
|

A wheel-shaped gallium-sulfide molecular ring with enhanced photocatalytic activity via indium alloying

Abstract: Wheel-shaped molecular rings are one of the most striking types of molecular aggregations due to their naturally aesthetically appealing architecture, giant size and interesting physical properties and potential applications. Meanwhile,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…16–18 These macrocyclic molecules exhibit distinct benefits in the optics, magnetism and host–guest chemistry domains. 19–23 Yang et al reported a {Nd 18 } molecular ring exhibiting NIR luminescence sensing of antibiotics. 24 Zheng et al synthesized the {Cr 8 Dy 8 } wheel, which is a single-molecule magnet.…”
Section: Introductionmentioning
confidence: 99%
“…16–18 These macrocyclic molecules exhibit distinct benefits in the optics, magnetism and host–guest chemistry domains. 19–23 Yang et al reported a {Nd 18 } molecular ring exhibiting NIR luminescence sensing of antibiotics. 24 Zheng et al synthesized the {Cr 8 Dy 8 } wheel, which is a single-molecule magnet.…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline porous metal–organic frameworks (MOFs), as a kind of emerging new materials with structural diversity, designability, tailorability and ultrahigh-specific surface area, have gradually become a hot research topic in coordination chemistry and materials science community because of their various topological structures and physicochemical properties. Up to now, a large number of developed MOFs were found to have promising applications such as catalysis, adsorption, and fluorescence recognition. Catalysis has been one of the most rapidly developing application fields because of the high density and uniformly dispersed catalytic active sites in the confined space of MOFs, which can be regulated under the guidance of reticular chemistry. Therefore, expected frameworks can be obtained by changing the type of metal nodes and/or ligands. So far, although the unique geometric characteristics of transition metal ions can promote the design of unique MOF networks, the design of highly coordinated porous solids is still a challenge because the enthalpy factor of transition metals is conducive to the formation of dense materials.…”
Section: Introductionmentioning
confidence: 99%